LITERATURE AS A SCIENTIFIC REFRAIN: A STUDY OF JOHN LARA’S THE SAMARITAN AND HENRIK IBSEN’S AN ENEMY OF THE PEOPLE: EDUCATION - Kanaa, Muriungi (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
attached is my abstract for your consideration. regards